(3GdbhGYO GdabgjI GdeJYdbI HGdSjGSI GdTQYjI h JWHjbGJgG GdeYGUQI (B: s (3OQGSI abgjI ebGQfI (B/ s - (3LgGO YHOGdMejO CMeO jhSa gfOGhis; (3EHQGgje YHOGdQMje (B: s ((3GdbGgQI (B: s (3LgGO YHOGdMejO CMeO jhSa gfOGhi (B: s, 2021)
(3jYfi GdHMK HOQGSI GdbhGYO GdabgjI GdVGHWI ddSjGSI GdTQYjI ai GdfhGRd h GdeSJLOGJ GdeYGUQI; h ef CeKdI Jdc GdfhGRd(B: (3JhMjO GdCPGf(B: (3h MeGjI OhQ GdYHGOI(B: (3h GdEdRGe HNWHI ehMOI ddLeYI(B: (3JYWjd GdLeYI h GdLeGYGJ h GdYeQI(B: (3h EZdGb GdeSGLO h GdMQejf GdTQjajf dJaTi GdhHGA(B: (3SdWI hdi GdCeQ ai EKHGJ GdCgdI HGdMSGHGJ GdadcjI(B: (3JbjjO GdML h GdYeQI Yf WQjb GdHhGHI GdEdcJQhfjI GdLOjOI (B"(3HhGHI GdYeQI GdeUQjI(B": (3Mce aQV QShe JcQGQ GdYeQI Ydi GdeYJeQjf(B: (3GdJhSYI GdQCSjI ddeSYi(B: (3SdWI hdi GdCeQ ai GdEdRGe HGdJHGYO Hjf GdeUdjf HSHH GfJTGQ GdhHGA(B: (3ELQGA GdYbhO HBdGJ GdGJUGd GdMOjKI(B: (3SdWI hdi GdCeQ ai JMOjO GdCSYGQ (B((3GdJSYjQ(B): (3GdYedGJ GdEdcJQhfjI GdQbejI GdeTaQI (B((3GdHJchjf(B): (3ENaGA GdRhGL h YOe JhKjbg(B: (3SdWI hdi GdCeQ ai JLQje RhGL GdbGUQGJ h JMOjO Sf GdRhGL(B: (3EdRGe GdebHdjf Ydi GdRhGL HGdaMU GdWHi bHd EJeGe GdYbO(B: (3GdWdGb GdeYdb(B: (3JbOjQ fabI GdRhLI GdYUQjI ai VhA GdbhGYO GdabgjI(B: (3SdWI hdi GdCeQ ai JTOjO YbhHI GdJMQT GdLfSi(B: (3SdWI hdi GdCeQ ai JTQjY GdbJd GdQMje Ch efYg(B: (3JTQjY EbGeI OYhi GdMSHI dGROQGA GdCOjGf(B: (3GdbhGYO GdabgjI GdVGHWI ddSjGSI GdTQYjI ai EUdGM GdaSGO GdacQi(B: (3SdWI hdi GdCeQ ai MXQ (B"(3GdJhc Jhc(B" (3h EMdGd (B"(3Gdejfi aGf(B" (3HOjkdG Yfg(B. (3Cge GdfJGFL GdJWHjbjI GdJi Je GdJhUd EdjgG(B: (3GdHMK GdeYGUQ bO CaGO ef GdbhGYO GdabgjI ai HMK fhGRd GdYUQ h eSGFdg HOQLI cHjQI; HMjK dG jSJWjY HGMK Cf jSJZfi Yf Jdc GdbhGYO GdabgjI ai HMK fhGRd GdYUQs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe GdTQjYI GdESdGejIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJHGYO Hjf GdeUdjfs; (3JYWjd GdLeYIs; (3JhMjO GdCPGfs